Impact of governance and technological progress on internet banking adoption across two major 21st century crises - Iulia Cristina Iuga (Cogent Business & Management)
This study explores the relationship between governance, technological progress, and internet banking adoption in the European Union (EU) from 2000 to 2023, focusing on the global financial crisis of 2008 and the COVID-19 pandemic. Employing a dynamic system GMM methodology, the analysis highlights the pivotal roles of governance quality and technological advancements in driving internet banking adoption. A key contribution of this research lies in its comparative analysis of the two crises. The findings reveal that governance priorities evolved from financial stabilization during the 2008 crisis to fostering digital transformation and cybersecurity during the COVID-19 pandemic. The study also demonstrates the synergistic effects of governance and technological infrastructure in reducing the digital divide, especially in EU states with historically low adoption rates. The practical implications of this research highlight how governance quality and technological advancements collectively influence internet banking adoption. Strengthening regulatory frameworks and improving digital security measures are essential for fostering trust and confidence in digital banking systems. Additionally, the findings emphasize the role of technological infrastructure in expanding access, particularly through enhanced broadband and mobile connectivity, which can drive digital banking even in regions with weaker governance indicators.